Empirical exploration of relationship between Ethical leadership and CSR in Manufacturing Sector in India - Dr. Sushmita Goswami, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The study aims to empirically explore the underlying relationship between leadership and CSR with a special reference to manufacturing sector in India.For this study Descriptive research design was being used. Formulated hypothesis were tested by sample based methods, using questionnaire and convenience sampling method. A sample size of 335 senior and middle level employees of the manufacturing companies of Delhi and North central region (NCR) was analyzed using ANOVA using SPSS 22 to test the proposed hypothesis. Based on the findings the study indicates that there is a significant impact of leadership on CSR activities in manufacturing sector organisations in Delhi and North central region (NCR). It is to note that there is great importance of leaders in manufacturing sector.The present research work emphasizes on the growing importance of efficient and strong leadership that can influence the magnitude and direction of various CSR activities for the welfare of the society.